Fetoscopic laser ablation for severe twin to twin transfusion syndrome: factors influencing perinatal outcome; including 'learning' curve of the procedure – lessons for new centres. (16th November 2010) - Morris, RK; Selman, TJ; Harbidge, A; Martin, WL; Kilby, MD
Abstract : Aim: To evaluate the effects of operator experience on perinatal outcome in a single centre. Methods: A cohort of consecutive monochorionic twin (MC) pregnancies complicated by severe twin to twin transfusion syndrome (TTTS) (≤26 weeks) treated by fetoscopic laser ablation (FLA) (October 2004 to November 2009). Results: Of the 164 MC twins; 5% were Quintero stage II, 79% stage III and 16% stage IV. The median gestational age (GA) at FLA was 20+2 weeks (95% CI 16 to 25+3). The median interval from FLA to delivery was 88.5 days (7 to 127) and GA of live born 33+5 weeks (28+2 to 36+1). Excluding pregnancy losses <24 weeks 100% of pregnancies had one live birth. In the first half (n=82) of the cohort, in 13% there were no survivors, in 55% both twins survived to birth, 43% both twins survived to 28 days postdelivery (at least one survivor in 76%). In the second half (n=82), corresponding values were 6%, 37%, 33% and 79%. Univariate logistic regression analysis indicated that lower Quintero stage (OR 3.84 (1.55 to 9.54)) and prolongation of GA increased survival of the twins (OR 0.75 (0.63 to 0.89), p<0.01). Increasing operator experience led to a significant reduction in perinatal death (OR 0.28 (0.1 to 0.74), p<0.01). GA at delivery (OR 0.93 (0.89 to 0.97), p≤0.01) was the only significant predictor of cerebral morbidity. Changes in use of trochar portals, selectivity of procedure and ablation at peripheral margins of the placenta will be described. Conclusion: These data indicate that relatively large numbers treated and experience with FLA minimises adverse outcome in MC pregnancies with severe TTTS.